1997
DOI: 10.1046/j.1537-2995.1997.37597293876.x
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of platelet storage conditions by using new polyolefin containers

Abstract: The new oxygen-permeable containers showed platelet quality comparable to that with the PL-732 and for longer storage periods and at higher platelet counts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
49
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 23 publications
3
49
0
Order By: Relevance
“…Certainly, red cell storage studies showed the di(2-ethylhexyl) phthalate plasticizer helps maintain red cell viability during storage. 27,28 In vitro platelet assays suggest that the storage bag [29][30][31][32] and even the method of bag sterilization 33 may affect platelet quality during storage. When Terumo BCT platelets were stored in Haemonetics CLX bags, there were clear improvements in poststorage platelet viability, but the results may still not be as good as Haemonetics platelets stored in Haemonetics CLX bags (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Certainly, red cell storage studies showed the di(2-ethylhexyl) phthalate plasticizer helps maintain red cell viability during storage. 27,28 In vitro platelet assays suggest that the storage bag [29][30][31][32] and even the method of bag sterilization 33 may affect platelet quality during storage. When Terumo BCT platelets were stored in Haemonetics CLX bags, there were clear improvements in poststorage platelet viability, but the results may still not be as good as Haemonetics platelets stored in Haemonetics CLX bags (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…For sufficient supply of oxygen both the total surface and the gas permeability per unit of surface area of the container are important [6, 7, 8]. Thus, the total number of platelets that can be stored adequately in a container depends on the pO 2 and pCO 2 diffusion capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the total number of platelets that can be stored adequately in a container depends on the pO 2 and pCO 2 diffusion capacity. When a certain maximum number is exceeded, platelet metabolism will switch to anaerobic glycolysis resulting in rapid acidification of the medium [6, 7, 8]. …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations